MODEL KONSEP TEORI KEPERAWATAN MADELEINE LEININGER DENGAN FRAKTUR - Anita Setyawati; Irna Nursanti (Yayasan Nusantara Hasana Berdikari, 2024)
Madeleine Leininger's Nursing Theory Concept Model, known as Transcultural Nursing Theory or Cultural Nursing Theory, provides a foundation for providing nursing care that focuses on the patient's cultural diversity. In the context of fractures, application of this theory can increase nurses' understanding of the influence of culture on patient perceptions, experiences, and responses to fracture injuries. This theory emphasizes the importance of care that is sensitive to cultural diversity in planning, implementing, and evaluating nursing care. In the case of fractures, cultural aspects can influence how patients view the disease, treatment options, and tolerance for pain. Therefore, nurses need to integrate patient cultural knowledge into nursing care planning to ensure the delivery of care that is effective and focused on individual needs. This conceptual model includes four subsystems of transcultural nursing, namely the ethnohistorical subsystem, kinetic-dynamic subsystem, linguistic subsystem, and social subsystem. In the context of fractures, nurses can use this approach to understand how cultural values, norms, and beliefs may influence the patient's healing and recovery process.